Perumusan Konsep Entitas Akuntansi Islam - Jaka Isgiyarta (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2009)
Business entity is a fundamental concept in developing financial reporting. Defi¬nition of element financial reporting, relationships among element financial reporting, relationship between firm and the owners is developed base on business entity concept. Conventional accounting is developed in capitalistic culture environment. Owner is as centre of firm. In other way, Islamic cultural is different with capitalistic culture. In Islamic business, society is centre of business, business for the society, the owner should not be centre of business. Business must be self reliant, it can do anything as person. So, Islamic accounting business entity must different with conventional accounting business entity. Keyword: Islamic accounting, conventional accounting, and business entity concept.